EFFECTIVENESS OF PLANNING ON THE DELIVERY OF PRIMARY HEALTHCARE IN NORTH CENTRAL NIGERIA - Yusuf, Gideon; Gambo, Nasamu; Ogedengbe, Frank Alaba (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Health as often said is a fundamental human right for every being. Therefore, ensuring the delivery of quality healthcare remains a pertinent focus of every government especially in the North Central Nigeria which is the main focus of this paper. Globally today, there is a universal consensus that no organization can effectively function and achieve and their goals and objectives without a robust, in-depth and effective yet flexible planning mechanisms else the become redundant and reactive rather than proactive which potentially hampers the quality of healthcare delivery in healthcare facilities. This study will employ a convergent parallel mixed-methods design. This rigorous approach involves the concurrent, but separate, collection and analysis of quantitative and qualitative data streams, with the explicit intention of merging the findings to draw well-substantiated meta-inferences. The core strength of this design lies in its ability to provide complementary strengths and non-overlapping weaknesses. This paper’s strategic intention is to effectively and efficiently explore how effective planning in healthcare influence the delivery of healthcare in primary healthcare facilities across the North Central part of Nigeria.